HISTOPATHOLOGICAL CONDITION OF MALE RAT LIVER INDUCED BY CONDENSED TANNIN EXTRACT OF BELUNTAS LEAVE - Eko Susetyarini; Fadiatul Ainiah; Fendy Hardian Permana (Jurnal Biosilampari : Jurnal Biologi, 2022)
This study at to determine the changes in liver histology of male rats after induction of condensed tannin extract of Beluntas leaves with control doses, 0.4 ml/kgBW, 2 ml/kgBW, and 3 ml/kgBW. This study is an experimental study for 14 days involving 24 samples of male rats. Parameters of histological structure changes were assessed by the scoring system for normal hepatocyte cell condition, parenchymatous degeneration, hydropic degeneration, and necrosis. One Way Anova test obtained a p value< 0.001 which means there was a significant difference in changes in the histopathological structure of liver cells significantly. Based on the Post Hoc test, it was obtained. between the control and treatment groups showed a significant difference between the control dose of 0.4 ml/kgBW, 2 ml/KgBW dose, and 3ml/KgBW dose. Meanwhile, the changes in liver histopathology between 2 ml/KgBW, and a dose of 3ml/KgBW were significantly the same.